2018
DOI: 10.1111/sum.12431
|View full text |Cite
|
Sign up to set email alerts
|

The transition from arable lands to rubber tree plantations in northern Thailand impacts weed assemblages and soil physical properties

Abstract: In South‐East Asia, rapid land use changes in recent decades have raised concerns for biodiversity and soil conservation. Weeds provide many ecosystemic services for soil protection and support biodiversity, and could mitigate the negative effects of intensification. We investigated the changes in weed assemblages and weed–soil interactions on a chronosequence from annual crops to mature rubber tree plantations. We sampled five fields for each of four land uses in mountainous northern Thailand (rainfed upland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…The CCA ordination analysis can effectively perform statistical tests on multiple environmental indicators under different environmental gradients and thus better reflects the relation between the species diversity of the community and environment. In this study, CCA ordination showed that soil water content and soil total potassium were factors with the greatest effect on the weed communities, which is consistent with several previous studies ( Ibell, Xu & Blumfield, 2010 ; Neyret et al, 2018 ). Moreover, the first two CCA axis explained the variance in the species-environment relationship, showing a comparatively better result.…”
Section: Discussionsupporting
confidence: 92%
“…The CCA ordination analysis can effectively perform statistical tests on multiple environmental indicators under different environmental gradients and thus better reflects the relation between the species diversity of the community and environment. In this study, CCA ordination showed that soil water content and soil total potassium were factors with the greatest effect on the weed communities, which is consistent with several previous studies ( Ibell, Xu & Blumfield, 2010 ; Neyret et al, 2018 ). Moreover, the first two CCA axis explained the variance in the species-environment relationship, showing a comparatively better result.…”
Section: Discussionsupporting
confidence: 92%
“…pigweed) mixture in Iran (Gholamhoseini et al, 2013a;Gholamhoseini et al, 2013b) and (2) a system with no tillage and weed cover mulching vs conventional tillage (Yagioka et al, 2015), other field studies also found that weed communities reduce nitrate leaching. Weeds may also contribute to regulate soil erosion by wind or water, but studies on this topic are scarce (Blavet et al, 2009;Lenka et al, 2017;Blaix et al, 2018;Neyret et al, 2018;Liu et al, 2019). Indeed, similarly to crop plants, the leaves of weed plants intercept raindrops thereby reducing splash erosion, their stems may reduce runoff velocity, and their roots may enhance soil shear strength and stability while favouring water infiltration (Kervroëdan et al, 2018;Neyret et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One consisted of continuous maize cultivation (either continuous maize monoculture or intercrop between tree rows) and the other with alternating cultivation of maize and rice. Neyret et al (2018) reported higher richness and greater diversity of weed communities in upland rice than in maize. A similar result is demonstrated here, in crop sequences containing upland rice and in sequences of only maize.…”
Section: Crop Sequence Variabilitymentioning
confidence: 97%
“…Maize was sown in densities of 31 000 hill/ha, with two plants per hill, which was in the low range of typical sowing densities (20 000 hill/ha to 80 000 hill/ha). In both maize and rice glyphosate was the most common herbicide, applied with rates ranging from 0.7 L/ha to 25 L/ha (at 480 g/L) and often in combination with other herbicides such as paraquat or atrazine (Neyret et al, 2018). These values, displaying a surprisingly large range, were reported by farmers but could not be checked in the field.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation